Making the most of super-diversity: notes on the potential of a new approach. (27th October 2017) - Magazzini, Tina
Abstract : This article aims at exploring how 'super-diversity' can cover aspects of current debates that traditional ways of understanding identity and multiculturalism could not. I start by engaging with Gilles Deleuze's differential ontology, which conceptualises difference as an inherent feature of identity and not some 'issue' brought by migration flows. I then outline super-diversity's potential implications for diversity management, with particular attention to the case of Roma minorities in Europe. The main argument is that super-diversity can provide a promising framework to address some of multiculturalism's constraints, if we focus on the new kind, rather than the new level, of complexity.